2023
DOI: 10.34190/ejel.21.2.2653
|View full text |Cite
|
Sign up to set email alerts
|

Creative Problem Solving Process Instructional Design in the Context of Blended Learning in Higher Education

Abstract: The Creative Problem Solving (CPS) process is a conceptual model that focuses on using higher-order thinking skills in order to overcome authentic problems during learning. The CPS process offers a structured methodology to enhance every learner's solid critical, creative, and innovative thinking skill. The application of the CPS method has been growing, including its implementation in the blended learning environment in universities. However, its application still requires a strategic framework that is by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…However, a universal shift to fully technology-driven learning faces resistance (Mirata et al, 2022). Educators, adopting a flexible approach, blend e-learning with traditional methods to strike a balance (Atwa et al, 2022;Ebbini, 2023;Setyosari et al, 2023). This flexible approach, combining computer technology, the Internet, and traditional methods, caters to diverse learning styles and promotes student interaction (Rasmitadila et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…However, a universal shift to fully technology-driven learning faces resistance (Mirata et al, 2022). Educators, adopting a flexible approach, blend e-learning with traditional methods to strike a balance (Atwa et al, 2022;Ebbini, 2023;Setyosari et al, 2023). This flexible approach, combining computer technology, the Internet, and traditional methods, caters to diverse learning styles and promotes student interaction (Rasmitadila et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A groundbreaking study by Song & Yi (2020) demonstrated the impact of virtual reality (VR) experiences, providing immersive learning environments that enhanced students' comprehension of reproductive behaviors in different animal species. Further, a research by (Nurrijal, Punaji Setyosari, Dedi Kuswandi, & Saida Ulfa, 2023) underscored the benefits of blended learning approaches, combining traditional teaching methods with video content, which resulted in better retention of information and conceptual clarity. Lastly, a study by Coşkun (2021) focused on the role of social media platforms as educational tools, presenting animal reproduction content through story-telling and interactive posts, which significantly increased student motivation and participation in class discussions.…”
Section: Introductionmentioning
confidence: 99%